2007
DOI: 10.1007/s10934-006-9094-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the porous structure of biodegradable scaffolds obtained with supercritical CO2 as foaming agent

Abstract: Poly(ε-caprolactone) foams were prepared, via a batch process, by using supercritical CO 2 as foaming agent. Their porous structure was characterized through mercury porosimetry, helium and mercury pycnometry, scanning electron microscopy (SEM) and X-ray microtomography observations coupled with image analysis. The pore size distributions obtained by these two latter techniques show that the pore structure is more homogeneous when the foaming process is performed under a high CO 2 saturation pressure (higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…Few studies have been reported about the solid-state scCO 2 foaming of PCL, [10,16] whereas several investigations have been performed on the scCO 2 foaming of PCL at temperatures above its melting temperature. [11,17,18] Making this process suitable for the incorporation of heat labile molecules within the scaffold before the foaming process may represent a great challenge in TE; [7,9] in this work we focused on the solid-state foaming of PCL and PCL-HA nanocomposite and performed the entire process at 37 8C.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have been reported about the solid-state scCO 2 foaming of PCL, [10,16] whereas several investigations have been performed on the scCO 2 foaming of PCL at temperatures above its melting temperature. [11,17,18] Making this process suitable for the incorporation of heat labile molecules within the scaffold before the foaming process may represent a great challenge in TE; [7,9] in this work we focused on the solid-state foaming of PCL and PCL-HA nanocomposite and performed the entire process at 37 8C.…”
Section: Resultsmentioning
confidence: 99%
“…CT-based reconstruction methods can be applied to create real 3D models of the syntactic foams. CT-based reconstruction methods are used successfully in many different materials research fields such as the research of porous polymeric materials (foams) [14], and open celled and closed-cell metallic foams [15], [16]. Recently X-ray computed micro tomography has been applied on porous fuel Manuscript received May 8, 2014; revised July 31, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In order to create real 3D models from the syntactic foams the CT-based reconstruction methods can be applicable. CT-based reconstruction methods are used successfully in many different materials research fields as for example porous polymeric materials (foams) [14], open celled and closed-cell metallic foams [15][16]. Recently the X-ray computed microtomography has been applied on porous fuel cell materials [17] and soil samples [18].…”
Section: Introductionmentioning
confidence: 99%